Global longitudinal strain is associated with heart failure outcomes in hypertrophic cardiomyopathy. Issue 10 (8th February 2016) - Reant, Patricia; Mirabel, Mariana; Lloyd, Guy; Peyrou, Jérôme; Lopez Ayala, Jose-Maria; Dickie, Shaughan; Bulluck, Heeraj; Captur, Gabriella; Rosmini, Stefania; Guttmann, Oliver; Demetrescu, Camelia; Pantazis, Antonis; et al.
Abstract : Objective: We hypothesised that abnormal global longitudinal strain (GLS) would predict outcome in hypertrophic cardiomyopathy (HCM) better than current echocardiographic measures. Methods: Retrospective analysis of risk markers in relation to outcomes in 472 patients with HCM at a single tertiary institution (2006–2012). Exclusion criteria were left ventricular (LV) hypertrophy of other origin, patients in atrial fibrillation, lost to follow-up and insufficient image quality to perform strain analysis. Standardised echocardiogram recordings were reviewed and standard variables and LV GLS were measured. The primary end-point included all cardiac deaths, appropriate defibrillator shocks and heart failure (HF) admissions. The secondary end-point was death by HF and admissions related to HF. Results: Mean age was 50.0±15.0 years; 322 (68%) were men. At a median of 4.3 years (IQR 0.1–7.8) follow-up, 21 (4.4%) patients experienced cardiovascular death: 6 (1.3%) died from HF, 13 (2.7%) had sudden cardiac death and 2 (0.4%) died secondary to stroke. Four (0.8%) patients experienced appropriate defibrillator shock, and 13 (2.7%) were admitted for HF. On multivariate Fine–Gray proportional hazard analyses, GLS was significantly associated with the primary end-point (HR=0.90, 95% CI 0.83 to 0.98, p=0.018) independently of age, maximal provoked LV outflow-tract gradient and LV end-systolic volume. Moreover, GLS was particularly associated with the secondary end-point (HR=0.82, 95% CI 0.75 to 0.90, p<0.0001) independently of age, previous atrial fibrillation, New York Heart Association (NYHA) class III–IV, LV end-systolic volume, E/E′, and outflow-tract gradient. Survival curves confirmed that GLS was associated with HF events (GLS <15.6%, p=0.0035). Conclusions: In patients with HCM, reduced GLS is an independent factor associated with poor cardiac outcomes, and particularly HF outcomes.